2012
DOI: 10.1186/1475-9276-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Is self-rated health a valid measure to use in social inequities and health research? Evidence from the PAPFAM women’s data in six Arab countries

Abstract: IntroductionSome evidence from high-income countries suggests that self-rated health (SRH) is not a consistent predictor of objective health across social groups, and that its use may lead to inaccurate estimates of the effects of inequities on health. Given increased interest in studying and monitoring social inequities in health worldwide, the aim of the present study was to evaluate the validity of SRH as a consistent measure of health across socioeconomic categories in six Arab countries.MethodsWe employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…Self-assessed health is a frequently-used outcome in research on the social determinants of health (Abdulrahim & El Asmar, 2012; Mulvaney-Day et al, 2007; Rohrer et al, 2007) and was used in the current study. Adolescents reported on their physical health by answering the following: “How would you rate your overall physical health?” Response categories ranged from 0 = poor to 5 = excellent.…”
Section: Methodsmentioning
confidence: 99%
“…Self-assessed health is a frequently-used outcome in research on the social determinants of health (Abdulrahim & El Asmar, 2012; Mulvaney-Day et al, 2007; Rohrer et al, 2007) and was used in the current study. Adolescents reported on their physical health by answering the following: “How would you rate your overall physical health?” Response categories ranged from 0 = poor to 5 = excellent.…”
Section: Methodsmentioning
confidence: 99%
“…This measure has shown to be a reliable indicator for overall health status [27] in developed countries but also in most Arabic countries [28]. Comorbidities were recorded by asking participants if they suffered from chronic physician-diagnosed conditions such as hypertension, diabetes, etc.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 It is also one of the most frequently used health indicators in epidemiological studies. 21 In one study, participants who reported receiving less than 6 hours of sleep a night were at greater odds for poor/very poor selfrated health relative to those who received more than 6 hours of sleep a night. 22 Moreover, sleep inadequacy has been associated with poor self-rated health in both men and women of varying ages and race/ethnicities.…”
mentioning
confidence: 99%